Gender Differences at the Onset of Autoimmune Thyroid Diseases in Children and Adolescents - Calcaterra, Valeria (Front Endocrinol (Lausanne), 2020)
Background: The incidence of autoimmune thyroid diseases (ATD) may vary with the beginning of reproductive function, although few reports differentiate the incidence before and during the onset of puberty, examining gender bias. We analyzed onset of ATD in a pediatric population to assess gender differences in onset age, disease subtype, pubertal status, autoimmune co-morbidity, family history and treatment, focusing on the interaction between gender and pubertal stage. Patients and methods: We retrospectively recorded 382 children and adolescents with ATD. In each patient physical examination was considered. The presence of other associated autoimmune diseases (AAD) and familial predisposition was also recorded. Results: Predominant prevalence was noted in females compared to males (p < 0.001), both in Hashimoto's diseases (HD or HT) and Graves' disease (GD) (p < 0.001). Mean age at diagnosis showed no significant difference between sexes (p > 0.05). A higher prevalence in pubertal subjects was noted compared to prepubertal (p < 0.001, particularly HT in early and GD in late pubertal stage), without sexes difference intra-(prepubertal vs. pubertal) and inter-puberty groups (prepubertal vs. early pubertal vs. late pubertal). Both in HT and in GD, the prevalence of autoimmune associated diseases (AAD) was higher in males compared to females (p = 0.04), with similar distribution according to the pubertal maturation. The familial predisposition was similarly distributed in both genders (p > 0.05) and into pubertal stages (p > 0.05). Conclusions: Females are more prone to develop ATD during puberty, earlier in HT than in GD. The effect of puberty is not different between genders, suggesting the role of additional factors other than hormones. The screening for detection of ATD is recommended in all patients with positive family history and other autoimmune diseases, mostly in males. Considerations of gender in pediatrics could be important to define pathogenic mechanisms of ATD and to help in early diagnosis and clinical management.